Laser fuse additive manufacturing preparation method of memory alloy fiber implanted aluminum alloy self-healing material
Through the laser coaxial wire feed additive manufacturing method, combined with surface treatment and pretension and prestraining technology, the effective combination of memory alloy fibers and aluminum alloy matrix is achieved, solving the problem of improving the self-healing function and mechanical properties of the material, and significantly improving the interface bonding strength and self-healing ability.
Patent Information
- Application Number
- CN202411675643.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-21
AI Technical Summary
It is difficult for the prior art to effectively combine memory alloy fibers and aluminum alloy matrix to realize the self-healing function of the material, while improving the overall mechanical properties of the composite material.
Using laser coaxial wire feeding additive manufacturing method, the memory alloy fibers are surface treated and pretensioned and prestrained to woven into a twill braided structure at a specific angle, and the aluminum alloy and memory alloy fibers are deposited layer by layer under an inert atmosphere to ensure good bonding of the material and performance maintenance.
The interface bonding strength between memory alloy fiber and aluminum alloy matrix is significantly improved, and the uniform distribution and orientation arrangement of memory alloy fibers are achieved, and the self-healing ability and mechanical properties of the material are enhanced.
Smart Images

Figure CN119525733A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laser additive manufacturing, and in particular to a method for preparing a memory alloy fiber reinforced aluminum alloy self-healing composite material by utilizing a laser coaxial wire feeding method. Background Art
[0002] With the rapid development of modern industry, especially in high-tech fields such as aerospace, automobile manufacturing and electronic products, the requirements for material performance are increasing day by day. Among them, the demand for lightweight and high-strength materials is particularly urgent. Aluminum alloy has always been one of the preferred materials in these fields due to its low density, high specific strength and good processing performance. However, traditional aluminum alloys still have shortcomings in fatigue resistance and damage tolerance, which limits their use in some critical applications.
[0003] In order to overcome these defects, researchers began to explore various composite materials technologies. Among them, shape memory alloys (SMA) have attracted widespread attention due to their unique shape memory effect and superelasticity. SMA can restore its original shape by heating or unloading after being deformed by external force. This property makes the self-healing function of the material possible. However, it has always been a technical problem to effectively combine SMA with aluminum alloy matrix. The main challenges include insufficient interface bonding strength, uneven distribution of SMA, and oxidation problems during the preparation process.
[0004] Traditional composite material preparation methods, such as powder metallurgy and melt casting technology, face many difficulties when processing SMA reinforced aluminum alloy composites. Although powder metallurgy can achieve good component uniformity, it is difficult to control the orientation of SMA fibers and there is a problem of high porosity. The melt casting method is prone to excessive oxidation of SMA fibers or adverse reactions with the matrix, affecting the overall performance of the material. In addition, these methods also make it difficult to accurately control the spatial distribution of SMA fibers in the matrix, which is crucial to the self-healing function of the material.
[0005] In recent years, the development of additive manufacturing technology has provided new ideas for solving the above problems. Laser additive manufacturing has shown great potential in the field of composite material preparation due to its advantages such as precise control and high flexibility. However, there is still a lack of an additive manufacturing method that can effectively combine SMA fibers and aluminum alloy matrix and achieve self-healing function. Existing technologies still face many challenges in processing SMA / aluminum alloy composites, such as interface bonding, organizational uniformity, and process parameter optimization.
[0006] Therefore, developing a new additive manufacturing method that can effectively combine SMA fibers with aluminum alloy matrix, realize the self-healing function of the material, and improve the overall mechanical properties of the composite material has important theoretical significance and practical application value. This will not only promote the development of high-performance lightweight composite materials, but also provide new material solutions for high-end manufacturing industries such as aerospace and automobile manufacturing. Summary of the invention
[0007] The purpose of the present invention is to provide an additive manufacturing method for a memory alloy fiber reinforced aluminum alloy self-healing material to solve the technical problems existing in the prior art, such as insufficient interface bonding strength, uneven distribution of SMA fibers, degradation of SMA fiber performance, limitations of the preparation process, and insufficient self-healing ability.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] A method for additive manufacturing of a memory alloy fiber reinforced aluminum alloy self-healing material, characterized in that the method comprises the following steps:
[0010] Firstly, Al-Mg-Sc aluminum alloy is selected as the matrix material, and Ti-Ta-Zr memory alloy is selected as the reinforcing fiber.
[0011] The first step is to perform surface treatment on the Ti-Ta-Zr memory alloy fiber by using a HF-HNO3 mixed acid solution for controlled etching, which is intended to increase the surface roughness of the fiber, create micro-mechanical bite conditions, and improve the interface bonding strength with the aluminum alloy matrix.
[0012] The second step is to apply a predetermined tensile pre-strain to the surface-treated memory alloy fiber. This step is to activate the shape memory effect of the memory alloy and lay the foundation for the subsequent self-healing function.
[0013] The third step is to weave the pretreated memory alloy fibers into a twill weave structure with a specific angle. The weaving density is controlled so that the volume fraction of the memory alloy fibers in the composite material reaches a predetermined proportion. This structural design can provide stress closure capabilities in multiple directions while ensuring sufficient self-healing capabilities without excessively affecting the performance of the matrix alloy.
[0014] The fourth step is to prepare the composite material using the laser coaxial wire feeding additive manufacturing method. This step is carried out in an inert atmosphere to prevent material oxidation and adverse reactions. The specific operation is as follows:
[0015] First, the laser power, wire feed speed, and table movement speed are set. Then, the first layer of aluminum alloy is deposited, followed immediately by a pre-treated memory alloy fiber mesh. Next, the next layer of aluminum alloy is deposited and the memory alloy fiber mesh is laid, alternating until the desired thickness is reached. Throughout the manufacturing process, the laser power, wire feed speed, and process temperature are precisely controlled to ensure good bonding of the materials and retention of performance.
[0016] The fifth step is to post-process the prepared composite material. Heat treatment is performed to optimize the microstructure of the matrix alloy. Surface treatment is then performed to improve the surface quality.
[0017] Preferably, the Al-Mg-Sc aluminum alloy is an Al-5Mg-0.3Sc alloy, which has excellent strength, toughness and corrosion resistance. This alloy composition can provide good matrix properties for the composite material and has good compatibility with the memory alloy fiber.
[0018] Preferably, the Ti-Ta-Zr memory alloy is a Ti-20Ta-10Zr alloy, which has a wide phase transition temperature range and excellent superelasticity. This alloy composition can ensure that the memory alloy fiber maintains its shape memory effect and superelasticity in a wide temperature range, thereby enhancing the self-healing ability and adaptability of the composite material.
[0019] Preferably, the etching time in the first step is 30 seconds, and the temperature is controlled at 20-25° C. Such etching conditions can effectively increase the surface roughness of the memory alloy fiber without excessively damaging it, thereby providing good interface conditions for subsequent bonding with the aluminum alloy substrate.
[0020] Preferably, the pre-stretching strain in the second step is controlled at 1%. This pre-strain value can effectively activate the shape memory effect of the memory alloy without causing excessive deformation or damage to the fiber.
[0021] Preferably, the braiding angle in the third step is ±45°, and the volume fraction of the memory alloy fiber is controlled at 10%-20%. This braiding structure and fiber content can ensure that the composite material has sufficient self-healing ability while not excessively affecting the performance of the matrix alloy, thereby achieving the best balance of performance.
[0022] Preferably, in the fourth step, high-purity argon is used as an inert atmosphere, the laser power range is 1000-1500W, the wire feeding speed range is 5-10m / min, and the worktable moving speed range is 400-600mm / min. The selection of these process parameters can ensure that the material is well melted and bonded during the preparation process, while minimizing the occurrence of oxidation and adverse reactions.
[0023] Preferably, the heat treatment temperature in the fifth step is controlled at 350-400°C for 2-4 hours, and the surface treatment can be performed by sandblasting or polishing. This post-treatment process can effectively optimize the microstructure of the base alloy, release internal stress, and improve the surface quality of the material.
[0024] The beneficial effect of the present invention is that by adopting the above technical solution, the present invention significantly improves the interface bonding strength between the memory alloy fiber and the aluminum alloy matrix. According to the test, in the prepared composite material, the interface shear strength between the memory alloy fiber and the aluminum alloy matrix is increased by 40%-60%, and the tensile strength is increased by 20%-30% compared with the untreated composite material. At the same time, the present invention realizes the uniform distribution and directional arrangement of the memory alloy fiber, and adopts a twill weave structure with a specific angle and a layer-by-layer laying method to ensure that the distribution uniformity of the memory alloy fiber in the entire component reaches more than 90%, and the performance difference in different directions is reduced to less than 10%. In addition, the present invention effectively prevents the oxidation and adverse reactions of the memory alloy fiber. By performing laser coaxial wire feeding additive manufacturing in an inert atmosphere, the thickness of the surface oxide layer of the prepared memory alloy fiber does not exceed 50nm, and more than 95% of the phase change enthalpy is retained, proving that its shape memory effect is basically unaffected.
[0025] The present invention also optimizes the self-healing function, and the prepared composite material can self-heal cracks with a width of up to 100μm at room temperature, and after 100 fatigue cycles, it still maintains a self-healing efficiency of more than 80%. In terms of comprehensive performance, compared with materials prepared by traditional methods, the tensile strength of the composite material of the present invention is increased by 25%, the fracture toughness is increased by 35%, and the fatigue life is extended by more than 50%. Under the same stress level, the service life is 2-3 times that of ordinary aluminum alloys. Finally, the process of the present invention has good flexibility and applicability, and can directly manufacture components with complex functional structures such as internal cooling channels and lightweight structures, and by adjusting the process parameters, a flexible balance can be achieved between strength and self-healing ability. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the layered structure of the memory alloy fiber reinforced aluminum alloy composite material of the present invention.
[0027] Figure 2 This is a cross-sectional diagram of the distribution of the memory alloy fibers of the present invention in the aluminum alloy matrix.
[0028] Figure 3 It is a planar structural diagram of the memory alloy fiber grid of the present invention.
[0029] Markings in the figure: 1, substrate, 2, Al-Mg-Sc deposited layer, 3, Ti-20Ta-10Zr memory alloy fiber. DETAILED DESCRIPTION
[0030] The present invention will be further described in detail below in conjunction with specific examples. It should be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be regarded as limiting the present invention.
[0031] This embodiment provides an additive manufacturing preparation method for a memory alloy fiber reinforced aluminum alloy self-healing material. In terms of raw material selection, this embodiment uses Al-5Mg-0.3Sc alloy as the matrix material. The chemical composition (mass fraction) of the alloy is: Mg 5.0%, Sc 0.3%, Fe≤0.1%, Si≤0.1%, and the rest is Al. The reason for selecting this alloy as the matrix is that the addition of magnesium can significantly improve the strength and corrosion resistance of the aluminum alloy, and the addition of the rare earth element Sc can refine the grains and improve the high temperature performance of the alloy. At the same time, the alloy has good welding performance and forming performance, which is suitable for additive manufacturing process. The reinforcement uses Ti-20Ta-10Zr alloy as the memory alloy fiber. The chemical composition (mass fraction) of the alloy is: Ta 20%, Zr 10%, and the rest is Ti. The main consideration for selecting this alloy is that it has an appropriate phase transition temperature range and excellent superelasticity while maintaining good chemical stability. This composition ratio can provide sufficient strength and toughness while ensuring the shape memory effect.
[0032] In the actual preparation process, the memory alloy fiber needs to be surface treated first. The purpose of surface treatment is to clean the fiber surface, remove the surface oxide layer, and form an appropriate surface roughness to enhance the subsequent interface bonding strength with the substrate. The specific operation steps are as follows: First, prepare an acid etching solution of 2% HF-5% HNO3 in a fume hood. During the preparation process, place a 1000ml beaker in an ice water bath, add deionized water to the beaker to the 600ml mark, and then slowly add the hydrofluoric acid and nitric acid required for the ratio calculation, while stirring with a glass rod.
[0033] The Ti-20Ta-10Zr memory alloy fiber is immersed in the prepared etching solution for controlled etching. Temperature control of the etching process is crucial, and the solution temperature needs to be stabilized at 22±1°C. Temperature control can be achieved through a water bath. The etching time is precisely controlled at 30 seconds, and a timer is used for timing. The accuracy of time control directly affects the effect of surface treatment. Too short a time will lead to insufficient surface treatment, and too long a time may over-erode the fiber and reduce its mechanical properties. After etching is completed, use stainless steel tweezers to immediately remove the fiber and quickly immerse it in the prepared deionized water for the first rinse, then replace the water for the second and third rinses, each rinse time is 1 minute.
[0034] The rinsed fiber needs to be ultrasonically cleaned. Place the fiber in a beaker filled with anhydrous ethanol, and place the beaker in an ultrasonic cleaner. The frequency of ultrasonic cleaning is set to 40kHz, the power is set to 100W, and the cleaning time is 5 minutes. Ultrasonic cleaning can effectively remove impurities and reaction products remaining on the fiber surface, while promoting surface activation. After cleaning, take out the fiber and place it in a vacuum drying oven for drying. The temperature of the drying process is controlled at 60°C, the vacuum degree is maintained at -0.08MPa, and the drying time is 2 hours. This drying process can completely remove moisture and ethanol from the fiber surface, preparing for subsequent processing.
[0035] Pre-strain treatment is a key step in the preparation process and directly affects the self-healing properties of memory alloy fibers. The fibers were subjected to tensile pre-strain treatment using a universal testing machine, and the pre-strain amount was set to 1%. Before pre-strain treatment, the testing machine needs to be preheated for 20 minutes to ensure that the equipment is in a stable working state. Fix both ends of the fiber on the clamp of the testing machine, and the clamping force should be moderate to prevent the fiber from slipping during the stretching process and to avoid excessive clamping force causing local damage to the fiber. The pre-strain rate is controlled at 1 mm / min, which ensures uniform deformation without causing local stress concentration due to excessive deformation rate. During the test, a strain gauge is used to monitor the strain state of the fiber in real time. When the pre-strain amount reaches 1%, the loading is stopped immediately, and the strain state is maintained for 1 minute before unloading.
[0036] Fiber weaving is an important process step to achieve uniform distribution of memory alloy fibers in the matrix. This embodiment adopts a ±45° twill weaving structure, which can provide good self-healing effect while ensuring the isotropy of the material. Figure 3 As shown, the planar structure of the memory alloy fiber grid presents a continuous diamond shape, each of which is interwoven by multiple fiber lines 3 to form a high-strength, high-toughness network structure. The weaving process uses a dedicated weaving device to weave the pre-strained fibers according to the design pattern. During the weaving process, special attention should be paid to controlling the tension of the fibers. Maintaining moderate tension can ensure the stability of the weaving structure without causing additional deformation of the fibers. By precisely controlling the weaving parameters, the volume fraction of the memory alloy fiber reaches 15%. After weaving, the woven mesh needs to be inspected to ensure that there are no defects such as breakage and entanglement.
[0037] Additive manufacturing is the core process of the method of the present invention. The manufacturing process is carried out in a special inert gas protection chamber, which is filled with high-purity argon gas to normal pressure. The laser power of the laser coaxial wire feeding system is set to 1200W, the laser spot diameter is 3mm, the wire feeding speed is 15mm / s, and the workbench movement speed is 10mm / s. The setting of these parameters is based on a large number of preliminary experimental optimization results, which can ensure a good molten pool state and deposition quality. During the manufacturing process, inert gas (high-purity argon gas) is continuously introduced, and the flow rate is maintained at 15L / min to prevent material oxidation. The substrate preheating temperature is set to 150°C, which can reduce the generation of thermal stress and improve the quality of the deposited layer.
[0038] In the actual deposition process, Figure 1 As shown, firstly, a layer of aluminum alloy with a thickness of about 0.8 mm is deposited on the substrate as a transition layer. Then, the aluminum alloy layer 2 and the memory alloy fiber mesh 3 are alternately deposited. The deposition thickness of each layer of the alloy is controlled at about 0.5 mm, and after the fiber mesh is laid, it is ensured that it is completely immersed in the molten pool.
[0039] like Figure 2 As shown in the figure, in the cross section of the composite material, the bottom base layer 1 is an aluminum alloy matrix. The multi-layer arc structure 2 above represents the aluminum alloy layer, and the memory alloy fibers are embedded on the top of each deposited layer. The cross section of these memory alloy fibers 3 presents a regularly distributed circular cross section. This layered structure clearly shows the alternating distribution of the aluminum alloy matrix and the memory alloy fibers. The cross section of the memory alloy fibers can be observed on both sides of each layer of the arc structure, indicating that the fibers are distributed in a grid-like manner in the aluminum alloy layer. This structural design helps to improve the overall strength and self-healing ability of the material.
[0040] During the deposition process, the state of the molten pool needs to be monitored in real time, including its size, shape and stability. If the molten pool is unstable or spattering is observed, the process parameters should be adjusted in time. After each layer of deposition is completed, the surface quality should be checked to ensure that there are no obvious defects. If defects are found, they need to be repaired or remanufactured in a timely manner.
[0041] Temperature control is particularly important during the entire manufacturing process. In addition to preheating the substrate, the interlayer temperature also needs to be controlled. After each layer is deposited, wait for the temperature to drop below 200°C before depositing the next layer. This can avoid excessive heat input causing performance degradation of the memory alloy fiber. At the same time, attention should be paid to controlling the position accuracy when changing layers to ensure good bonding between the layers. After manufacturing is completed, the sample is cooled to room temperature with the furnace. This slow cooling process helps to release internal stress and improve the overall performance of the material.
[0042] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims and shall not be limited to the description of the above specific embodiments.
Claims
1. An additive manufacturing method for preparing a memory alloy fiber reinforced aluminum alloy self-healing material, characterized in that: The following steps are involved: (1) Select Al-Mg-Sc aluminum alloy as the matrix material; (2) The Ti-20Ta-10Zr memory alloy fiber is subjected to surface acid etching treatment to enhance its wettability; (3) applying a 1.0% tensile pre-strain to the treated memory alloy fiber to improve its restoring force; (4) weaving the memory alloy fibers into a twill weave structure; (5) A laser coaxial wire feeding method was used to prepare a multilayer composite material by alternately depositing aluminum alloy layers and laying memory alloy fiber layers by optimizing the fiber mesh structural parameters; the fiber mesh structure optimization included setting the fiber weaving angle to 45° to achieve uniform stress dispersion, controlling the longitudinal and transverse fiber spacing ratio to 1:1 to ensure isotropic stress transfer, and designing the overlap length of the fiber intersection to be no less than 10 times the fiber diameter to enhance the interlayer connection strength. At the same time, the laying directions of adjacent layers of fiber mesh were staggered by 90° to improve the interlayer shear resistance. The overall mechanical properties of the composite material were improved by optimizing the above structural parameters.
2. The preparation method according to claim 1, characterized in that: The acid etching process comprises: (a) The memory alloy fiber is immersed in a 2% HF-5% HNO3 aqueous solution; (b) Etching at room temperature for 30 seconds; (c) Rinse with distilled water and dry.
3. The preparation method according to claim 1, characterized in that: The laser coaxial wire feeding method comprises: (a) depositing a layer of Al-Mg-Sc aluminum alloy on a substrate; (b) laying a layer of woven memory alloy fibers on the aluminum alloy layer; (c) Repeat steps (a) and (b) until the designed thickness is reached.
4. The preparation method according to claim 1, characterized in that: The diameter of the Ti-20Ta-10Zr memory alloy fiber is 50 μm.
5. The preparation method according to claim 1, characterized in that: The reinforcing effect of the shape memory alloy fiber on the matrix includes that when the matrix is deformed or cracked by excessive load, the crack encounters the shape memory alloy fiber during the expansion of the matrix, and processes such as interface debonding, matrix and fiber breakage, and fiber pull-out may occur, making the fracture energy higher than that of a single aluminum alloy, thereby playing a strengthening role.
6. The preparation method according to claim 1, characterized in that: The process temperature of the laser coaxial wire feeding process is controlled between 660°C and 1400°C, ensuring that the Ti-20Ta-10Zr memory alloy fiber completes the phase transformation from the β phase to the ɑ″ phase in this temperature range, while ensuring that the aluminum alloy matrix is fully melted and forms a good interface bond with the fiber.
7. The preparation method according to claim 1, characterized in that: The self-healing process of the composite material includes: when the material is damaged by external force and cracks are generated, by heating to a temperature close to the solidus line of the Al-Mg-Sc alloy (about 600°C), the phase transformation from martensite (α″ phase) to austenite (β phase) in the memory alloy is activated, and the recovery stress generated by the shape memory effect is used to close the cracks, thereby realizing the self-healing of the material.
8. The preparation method according to claim 1, characterized in that: The memory alloy fiber mesh is formed by weaving multiple fiber filaments in parallel, and each main fiber is composed of multiple filaments in parallel. The density of the fiber mesh can be controlled by adjusting the number of parallel fiber filaments and the spacing between adjacent parallel fiber bundles, thereby achieving regulation of the self-healing ability of the composite material.
9. The preparation method according to claim 1, characterized in that: The composition of the Al-Mg-Sc aluminum alloy is as follows by mass percentage: Mg: 4.0-6.0%, Sc: 0.2-0.8%, and the remainder is Al and inevitable impurities.
Citation Information
Patent Citations
Double-pass bending type shape memory alloy composite material, manufacturing method and driving method
CN109760341A
Method for obtaining a part with self-healing properties, part with self-healing properties and method for repairing cracks of the part
CN110352103A
Products comprising reinforcing fibres and shape memory alloy wires and methods of making thereof
CN110809514A
Selective laser shock-additive composite manufacturing method for three-dimensional reinforced shape memory alloy
CN113414408A
Bulkhead with slot array for wireless communication in ship
KR1020250174209A
Cited By
FDM printing method for reinforcing bonding performance by filling compatibility reinforcing phase particles between layers
CN120863053A